2020
DOI: 10.3390/cancers12071827
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal MicroRNAs and Organotropism in Breast Cancer Metastasis

Abstract: Breast cancer is the most frequent malignancy for women in which one in eight women will be diagnosed with the disease in their lifetime. Despite advances made in treating primary breast cancer, there is still no effective treatment for metastatic breast cancer. Consequently, metastatic breast cancer is responsible for 90% of breast cancer-related deaths while only accounting for approximately one third of all breast cancer cases. To help develop effective treatments for metastatic breast cancer, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 139 publications
1
27
0
Order By: Relevance
“…Besides, the availability, abundance, and stability of exo‐miRNAs in biological fluids make it an ideal biomarker for various types of cancers (including OS; Wong et al, 2020). For example, plasma exo‐miR‐139‐3p is a novel biomarker for CRC (Liu, Yang, et al, 2020).…”
Section: Exosomal Ncrnasmentioning
confidence: 99%
“…Besides, the availability, abundance, and stability of exo‐miRNAs in biological fluids make it an ideal biomarker for various types of cancers (including OS; Wong et al, 2020). For example, plasma exo‐miR‐139‐3p is a novel biomarker for CRC (Liu, Yang, et al, 2020).…”
Section: Exosomal Ncrnasmentioning
confidence: 99%
“…Exosomes contain both proteins and micro-RNAs and as such, they can be key sources of both of these types of circulating biomarkers. A complete description of how exosomes act within bone metastatic cancers is beyond the scope of this review but it has been extensively described elsewhere [ 138 , 139 ].…”
Section: Biomarkers For Bone Metastasismentioning
confidence: 99%
“…Over the past years, small RNA regulators were discovered for the development of cancer research. MicroRNAs (miRNAs) are tiny single-stranded RNAs with 20 to 24 nucleotides that do not specifying the genetic codes [3] and are stabilized or located in post-transcription gene expression regulation in multicellular organisms [4]. Recent research has demonstrated that MicroRNAs are aberrantly represented in different forms of tumors [5].…”
Section: Introductionmentioning
confidence: 99%